Therapeutic benefits of delayed lithium administration in the neonatal rat after cerebral hypoxia-ischemia. - Cuicui Xie (Public Library of Science (PLoS), 2014)
Aim We have previously shown that lithium treatment immediately after hypoxia-ischemia (HI) in neonatal rats affords both short- and long-term neuroprotection. The aim of this study was to evaluate possible therapeutic benefits when lithium treatment was delayed 5 days, a time point when most cell death is over. Methods Eight-day-old male rats were subjected to unilateral HI and 2 mmol/kg lithium chloride was injected intraperitoneally 5 days after the insult. Additional lithium injections of 1 mmol/kg were administered at 24 h intervals for the next 14 days. Brain injury was evaluated 12 weeks after HI. Serum cytokine measurements and behavioral analysis were performed before sacrificing the animals. Results Brain injury, as indicated by tissue loss, was reduced by 38.7%, from 276.5±27.4 mm3 in the vehicle-treated group to 169.3±25.9 mm3 in the lithium-treated group 12 weeks after HI (p<0.01). Motor hyperactivity and anxiety-like behavior after HI were normalized by lithium treatment. Lithium treatment increased neurogenesis in the dentate gyrus as indicated by doublecortin labeling. Serum cytokine levels, including IL-1α, IL-1β, and IL-6, were still elevated as late as 5 weeks after HI, but lithium treatment normalized these cytokine levels. Conclusions Delayed lithium treatment conferred long-term neuroprotection in neonatal rats after HI, and this opens a new avenue for future development of treatment strategies for neonatal brain injury that can be administered after the acute injury phase.